ORGANIZACIÓN CONTABLE Y TRIBUTARIA DE LA CONTABILIDAD COMERCIAL Y PLANEACION DE UTILIDADES EN LA EMPRESA ALUMITEC DEL CANTON CATAMAYO PERIODO JULIO - DICIEMBRE DE 2011 - Jimenez Avila, Tania Noemi (2016)
The thesis called ACCOUNTING AND ORGANIZATION TAX OF BUSINESS ACCOUNTING AND PLANNING OF PROFITS IN THE COMPANY ALUMITEC CANTON CATAMAYO period July - December 2011 it made with the purpose of providing results attached to business reality and as a basis for decisions to promote their profitability. Its development contributed to fulfilling the objectives and reference design necessary to implement a tax accounting organization tools in an efficient way; the inventory, ledgers and accounting records to facilitate the control of operations to determine the financial statements and meet the economic and financial situation, with the aim of presenting the real value generated by the company, implement the main indicators to measure the situation economic, and present the projected income statement based on a macroeconomic index for the following financial year. To meet the above objectives was necessary to apply methods and techniques in order to obtain relevant information for each component and meet the objectives set for this number of interviews was conducted to the owner of the commercial, the source information was collected through bills of sale and purchase, and then select and organize them by date, and thus proceed with the accounting process that starts from the initial - 5 - inventory, until the financial statements were subject to the application of indicators to measure its economic positioning rear projection and accounting data based on the index of inflation for the year 2011. The accounting procedures are performed using the system of multiple goods account, which helped us to get the cost of selling the products offered and the gross profit obtained in the sale of the same, profit by subtracting values the costs incurred in the period net income was obtained, which is described in the financial statements submitted to complete the accounting period. The main results can be seen that the company makes a profit, liquidity, profitability and acceptable debt, which has allowed him to pay their expenses and short-term obligations smoothly, maintaining its reputation with suppliers and always careful in providing products and quality services to ensure their permanence in the market.